Principles of Good Administration under the European Code of Good Administrative Behavior - Batalli, Mirlinda; Fejzullahu, Artan (Pécs journal of international and European law, 2018)
The purpose of good administration and the conduct of administrative functions by the administration bodies are to provide citizens with the most efficient services by supporting and respecting the general interest of the society and the realization of human rights. Good administration has to be based on principles that serve as a basis for exercising the activities of the administration bodies. The EU member states and those states aspiring to be part of the European family are in constant effort to harmonize principles of good governance, an effort that derives from ideas for a common "European administrative space". Having this in mind, this paper aims to review: a) the basis of establishing principles of good administration in the European context, b) a description and review of a number of basic principles set out in the European Code of Good Administrative Behavior, and c) an explanation of the importance of implementing these principles from states that aim to have a good and efficient administration.